2017
DOI: 10.29299/kefad.2017.18.3.021
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Matematiğe Yönelik Duyuşsal Özellikleri İle Temel Eğitimden Ortaöğretime Geçiş (TEOG) Sınavları Öncesi Yaşadıkları Stresin Matematik Başarısına Etkisi

Abstract: Bu çalışma birinci yazarın doktora tezinden üretilmiştir. http://kefad.ahievran.edu.tr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
5
0
3
Order By: Relevance
“…Therefore, math anxiety can be reduced by using group dynamics. In the literature, it has been determined that there is a reversed relationship between math anxiety and math attitude (Kesici & Asilioglu, 2017;Rencber, 2011;Tuncer & Yilmaz, 2016;Yaratan & Kasapoglu, 2012). Therefore, pupils with math anxiety can benefit from group dynamics and develop positive attitudes towards math, via reducing anxiety levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, math anxiety can be reduced by using group dynamics. In the literature, it has been determined that there is a reversed relationship between math anxiety and math attitude (Kesici & Asilioglu, 2017;Rencber, 2011;Tuncer & Yilmaz, 2016;Yaratan & Kasapoglu, 2012). Therefore, pupils with math anxiety can benefit from group dynamics and develop positive attitudes towards math, via reducing anxiety levels.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, there are several studies showing that there is inverse relationship between academic achievement and math anxiety (Baloglu, 1999;Devine, Fawcett, Szűcs & Dowker, 2012;Kesici, 2016;Kilic, 2011;Lee & Stankov, 2013;Ma, 1999;Sad, Kis, Demir & Ozer, 2016;Yildirim, 2011). It has also been determined that mathematics anxiety is a significant predictor of success in math and negatively affects it (Akgul, 2008;Kesici & Asilioglu, 2017;Lee & Stankov, 2013;Shores & Shannon, 2007). Math anxiety causes pupils to avoid math (Yenilmez & Ozabaci, 2003) and to bunk off school (Kurum, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible reason may be the individual differences of the students rather than the facilities of the school [18]. When it comes to the details, it can be seen that many variables such as housing income, annual education expenditure for the child, education level of the parents (Aslan, 2017), attitude, motivation, pre-test stress level [9], anxiety [4], selective attention skills [21] number of siblings, having a study room [12] can play a role.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Aslan (2017), it is seen that the housing income, the annual education expenditure for the child and the education level of the parents predicted 30% of the TEOG scores (R 2 =.301). In the study conducted by Kesici and Asilioglu [9], the anxiety, attitude, motivation and pre-test stress level of the students indicate a significant relationship with TEOG mathematics achievement (R=.495; R 2 =.245, p<.05). It was found that these four variables explained 24.5% of the change in mathematics achievement together.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation